Thermal state of the active layer and permafrost along the Qinghai-Xizang (Tibet) Railway from 2006 to 2010 - Wu, Q.; Zhang, T.; Liu, Y. (The Cryosphere, 2018)
In this study, we investigated changes in active layer thickness (ALT) and permafrost temperatures at different depths using data from the permafrost monitoring network along the Qinghai-Xizang (Tibet) Railway (QXR) since 2005. Among these sites, mean ALT is ~3.1 m, with a range of ~1.1 to 5.9 m. From 2006 through 2010, ALT has increased at a rate of ~6.3 cm a −1 . The mean rate of permafrost temperature rise at the depth of 6.0 m is ~0.02 °C a −1 , estimated by linear regression using 5 yr of data, and the mean rate of mean annual ground temperature (MAGT) rise at a depth of zero amplitude is ~0.012 °C a −1 . Changes for colder permafrost (MAGT <−1.0 °C) are greater than changes for relatively warmer permafrost (MAGT >−1.0 °C). This is consistent with results observed in the Arctic and subarctic.